Pemikiran Pendidikan Menurut Az-Zarnuji - Suriadi (Program Pascasarjana Institut Agama Islam (IAI) Darullughah Wadda'wah Pasuruan, 2023)
This article discusses Islamic education thoughts according to Az-Zarnuji. Islamic education is expected to be able to shape students who can apply spiritual-religious values and ethics, but what is happening currently has not reached the intended goals. As a solution, there is a need for a renewal in the educational concept. This paper is written using the literature review method (library research). The findings reveal that Az-Zarnuji's educational thoughts are relevant to modern education in the following aspects. Educational Goals: The alignment with the national educational goals in the 2003 National Education System Law (Sisdiknas) regarding education goals, both emphasize morality, Educators: This can be observed through the teacher's personal competencies, which include a strong personality, noble ethics, wisdom, authority, and serving as an example for students. Students: Relevance can be seen in alignment with Sisdiknas Law number 23 of 2003, Chapter V, Article 12, which emphasizes students' responsibility to uphold educational norms. Curriculum: The foundation of the Islamic Education curriculum includes religious fundamentals and psychological bases. Teaching Methods: It is evident that memorization and discussion methods are still used in the current era, tailored to the students' needs.